Zgodovinske korenine čarobne pravljice - Propp, Vladimir (ZRC SAZU, Založba ZRC, 2022)
This translation of the book ('The Historical Roots of Magic Tale') written by one of the most prominent Russian folklorists of the 20th century Vladimir Yakovlevich Propp, presents one more classical work of anthropological and folkloristical science to Slovenian researchers. The theoretical starting-points which Propp concived in his book “Morphology of the Folktale” was in this work projected on concrete material – on Russian and European folktales. By comparing folktale motifs with actual historical and anthropological sources he substantiated his structuralistical and ritualistical theoties in folk narrative research and folkloristics.